Analisis Kelayakan Agroindustri Tape Handayani 82 Desa Nangkaan Kecamatan Bondowoso Kabupaten Bondowoso - Mizan Imam Al-Hakim; Istiqomah Sulasminingsih; Febriansyah Basta Adi Mulya (Universitas Islam Kadiri, 2022)
Cassava is a food plant in the form of shrubs with other names cassava, cassava or cassava. The most famous product of cassava processing is cassava tape so that Bondowoso is better known as the city of tape. Bondowoso is known as the city of tape and has several businesses in the culinary field, especially tape, one of the businesses known is Tape Handayani 82.The aim of this research is to determine the market, technical and technological aspects, as well as the management and organization of the Tape Handayani 82 agro-industry in Bondowoso, The second objective is to determine the financial aspects of the Tape Handayani 82 agro-industry in Bondowoso. The data collection method of this research is using observation, interview, documentation study, and literature study. The results of this research show that the marketing channels used are 2 simple marketing channels. The technology used uses traditional equipment. The application of the management concept uses 4 management functions. Based on the calculation of investment criteria, it shows that NPV (2.961.213.03> 0), Net B / C (2.16> 1), Gross B / C (1.37> 1), IRR (53% 9.95%), PR ( 2.16> 1) and the value of PP for 1 year 6 months 2 days indicates that agro-industrial activities are feasible to run.